Methodology matters when estimating deer abundance: a global systematic review and recommendations for improvements. Issue 4 (24th March 2022) - Forsyth, David M.; Comte, Sebastien; Davis, Naomi E.; Bengsen, Andrew J.; Côté, Steeve D.; Hewitt, David G.; Morellet, Nicolas; Mysterud, Atle
Abstract: Deer (Cervidae) are key components of many ecosystems and estimating deer abundance or density is important to understanding these roles. Many field methods have been used to estimate deer abundance and density, but the factors determining where, when, and why a method was used, and its usefulness, have not been investigated. We systematically reviewed journal articles published during 2004–2018 to evaluate spatio‐temporal trends in study objectives, methodologies, and deer abundance and density estimates, and determine how they varied with biophysical and anthropogenic attributes. We also reviewed the precision and bias of deer abundance estimation methods. We found 3, 870 deer abundance and density estimates. Most estimates (58%) were for white‐tailed deer ( Odocoileus virginianus ), red deer ( Cervus elaphus ), and roe deer ( Capreolus capreolus ). The 6 key methods used to estimate abundance and density were pedestrian sign (track or fecal) counts, pedestrian direct counts, vehicular direct counts, aerial direct counts, motion‐sensitive cameras, and harvest data. There were regional differences in the use of these methods, but a general pattern was a temporal shift from using harvest data, pedestrian direct counts, and aerial direct counts to using pedestrian sign counts and motion‐sensitive cameras. Only 32% of estimates were accompanied by a measure of precision. The most precise estimates were from vehicular spotlight counts and from capture–recapture analysis of images from motion‐sensitive cameras. For aerial direct counts, capture–recapture methods provided the most precise estimates. Bias was robustly assessed in only 16 studies. Most abundance estimates were negatively biased, but capture–recapture methods were the least biased. The usefulness of deer abundance and density estimates would be substantially improved by 1) reporting key methodological details, 2) robustly assessing bias, 3) reporting the precision of estimates, 4) using methods that increase and estimate detection probability, and 5) staying up to date on new methods. The automation of image analysis using machine learning should increase the accuracy and precision of abundance estimates from direct aerial counts (visible and thermal infrared, including from unmanned aerial vehicles [drones]) and motion‐sensitive cameras, and substantially reduce the time and cost burdens of manual image analysis. Abstract : A minority of deer abundance and density estimates were accompanied by a measure of precision, and bias was seldom evaluated. The usefulness of deer abundance and density estimates would be substantially improved by reporting key methodological details, robustly assessing bias, using methods that increase detection probability, and reporting the precision of estimates.